Waldgirmes, Deutschland: Abschluss der Arbeiten und Publikation - Rasbach, Gabriele (e-Forschungsberichte des DAI, 2023)
The long-term project of the Roman civil site in Waldgirmes, which dated to the late Augustan period, had provided new input to help understand the complexity of Romano-Germanic-affairs of this time. Waldgirmes shows that the territory beyond the Rhine was taking the first steps towards becoming a Roman province. The site has a few military elements, but mostly reflects aspects of different civil and rural communities. Waldgirmes is located at the river Lahn and about 7 km southwest of the late Iron Age oppidum on the Dünsberg. At the current state of research this pre-Roman settlement ended around 30/15 BC, so a few years before the Roman occupation in the Germania. Surprisingly the settlement was not abandoned immediately after the defeat of Varus in AD 9, but probably continued in use until AD 16. In spring 2016, the first volume concerning the project’s results was published.